Describing novel mitochondrial genomes of Antarctic amphipods. Issue 5 (4th May 2022) - Salabao, Louraine; Plevoets, Tim; Frédérich, Bruno; Lepoint, Gilles; Kochzius, Marc; Schön, Isa
Abstract: To date, only one mitogenome from an Antarctic amphipod has been published. Here, novel complete mitochondrial genomes (mitogenomes) of two morphospecies are assembled, namely, Charcotia amundseni and Eusirus giganteus . For the latter species, we have assembled two mitogenomes from different genetic clades of this species. The lengths of Eusirus and Charcotia mitogenomes range from 15, 534 to 15, 619 base pairs and their mitogenomes are composed of 13 protein coding genes, 22 transfer RNAs, 2 ribosomal RNAs, and 1 putative control region CR. Some tRNAs display aberrant structures suggesting that minimalization is also ongoing in amphipod mitogenomes. The novel mitogenomes of the two Antarctic species have features distinguishing them from other amphipod mitogenomes such as a lower AT-richness in the whole mitogenomes and a negative GC- skew in both strands of protein coding genes. The genetically most variable mitochondrial regions of amphipods are nad6 and atp8, while cox1 shows low nucleotide diversity among closely and more distantly related species. In comparison to the pancrustacean mitochondrial ground pattern, E. giganteus shows a translocation of the nad1 gene, while cytb and nad6 genes are translocated in C. amundseni . Phylogenetic analysis based on mitogenomes illustrates that Eusirus and Charcotia cluster together with other species belonging to the same amphipod superfamilies. In the absence of reference nuclear genomes, mitogenomes can be useful to develop markers for studying population genetics or evolutionary relationships at higher taxonomic levels.